2003
DOI: 10.3732/ajb.90.1.78
|View full text |Cite
|
Sign up to set email alerts
|

Asynchronous development of stigmatic receptivity in the pear (Pyrus communis; Rosaceae) flower

Abstract: While stigma anatomy is well documented for a good number of species, little information is available on the acquisition and cessation of stigmatic receptivity. The aim of this work is to characterize the development of stigma receptivity, from anthesis to stigma degeneration, in the pentacarpellar pear (Pyrus communis) flower. Stigma development and stigmatic receptivity were monitored over two consecutive years, as the capacity of the stigmas to offer support for pollen germination and pollen tube growth. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 52 publications
3
32
0
Order By: Relevance
“…Although this is a trait common for pear cultivars, 'Ingeborg' fruit set and yield seem to be especially affected depending on season and possibly microclimate, as shown by stark differences in yield between orchards in the same region. Furthermore, Sanzol et al (2003) demonstrated clearly that asynchronous maturation of the both stigmas and ovules within a single ovary in the same pear flower can occur and varies between years. This probably means that EPP is long enough to ensure the pollination and fertilization in pears.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is a trait common for pear cultivars, 'Ingeborg' fruit set and yield seem to be especially affected depending on season and possibly microclimate, as shown by stark differences in yield between orchards in the same region. Furthermore, Sanzol et al (2003) demonstrated clearly that asynchronous maturation of the both stigmas and ovules within a single ovary in the same pear flower can occur and varies between years. This probably means that EPP is long enough to ensure the pollination and fertilization in pears.…”
Section: Resultsmentioning
confidence: 99%
“…This probably means that EPP is long enough to ensure the pollination and fertilization in pears. According to Sanzol et al (2003), this aspect is even more pronounced in populations where pollinator efficiency is low, unreliable pollination conditions exist, or both. This certainly appears to be the case in the Hardanger region.…”
Section: Resultsmentioning
confidence: 99%
“…For example, on immature stigmas of pear flowers, mature pollen can adhere but do not hydrate and germinate. On a degenerating stigma, pollen can adhere, hydrate, and germinate, but pollen tube growth arrests abruptly (Sanzol et al, 2003). A cuticle of varying thickness is deposited on most stigmas above the epidermis, and compatible pollen deposited on a heavily cutinized surface never germinates (HeslopHarrison, 2000).…”
Section: Pollen-stigma Interactionsmentioning
confidence: 99%
“…As in the current study, stigma receptivity was monitored in pear as the capacity to offer support for pollen germination and pollen tube growth (Sanzol et al 2003b). Immature pear flowers' stigmas can support adhesion of pollen on their surface, but cannot provide a substrate for pollen hydration and germination (Sanzol et al 2003b), which confirms that pollen germination is a more appropriate measure of pollen receptivity. Olive flowers exhibited early stigma receptivity, showing high percentages of pollen germination at anthesis (Table 1).…”
Section: Discussionmentioning
confidence: 89%